Determinan Penggunaan Metode Kontrasepsi IUD di Indonesia Analisis Data SDKI 2002-2003 - Rosyati Pastuti, Siswanto Agus Wilopo (Berita Kedokteran Masyarakat (BKM), 2007)
Background: Report of Indonesian Health and Demographic Survey (IHDS) 2002-2003 showed an increase of contraceptive use from 57% (1997) to 60% (2002-2003) among married women in Indonesia. The use of Injection method had the highest increase while Intra Uterine Device was decrease. Contraceptive method usually was used based on the reasons for controlling birth and birth spacing. The choice of contraceptive method was influenced by motivation, access and cost.Objective: The goal was to explore the determinant of IUD method use in Indonesia.Method: Data of IHDS 2002-2003 was analyzed using cross-sectional study design. Sample was married women aged 15-49 years old who use IUD method. Data was analyzed statistically using chi-square test and logistic regression at 95% significant level.Result: Logistic regression analysis showed a significant relationship between the demand of contraceptive use and IUD method use. Respondent with birth control reason had a probability of 2.8 times to use IUD (OR=2.8; CI 95%=2.45-3.13). Health service place and cost of service were also had a significant relationship with contraceptive use demand. Respondent who used government’s health facility had a probability to use IUD OR=1.9; CI 95%=1.67-2.06).Conclusion: Respondent with birth control reason tends to use IUD. Those who use government’s health facility and those who paid more than Rp200.000,00 were also tend to use IUD. Another factors influence IUD method use was age, parity, education level, economic status and residence status.Keywords: IUD, family planning, birth spacing